2020
DOI: 10.21203/rs.3.rs-50231/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clonal Expansion of Bone Marrow CD8+ T Cells in Acute Myeloid Leukemia Patients at New Diagnosis and Post Chemotherapy

Abstract: Background: CD8+ T cells are crucial adaptive immune effectors and express receptors (T cell receptors, TCRs) that specifically recognize and eradicate tumor cells. The diversity of the TCR repertoire is generated by specialized genetic diversification mechanisms, leading to an extremely variable TCR repertoire capable of recognizing a wide range of antigens. However, the variations in CD8+ TCR diversity and their clinical implications in AML patients remain unknown.Methods: CD8+ T cells in 10 healthy donors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Lower diversity of the TCR repertoire may reflect more recognition of certain specific antigen and less responses to diversified antigens. Such restricted recognition implied T cell clones targeting these antigens undergo expansion, which is also called clonal expansion (29). Subsequently, we assessed the gene usage in these two distinct groups.…”
Section: Restricted Tcr Clonotypes Were Revealed In Pgd Compared With Ngd Patientsmentioning
confidence: 99%
“…Lower diversity of the TCR repertoire may reflect more recognition of certain specific antigen and less responses to diversified antigens. Such restricted recognition implied T cell clones targeting these antigens undergo expansion, which is also called clonal expansion (29). Subsequently, we assessed the gene usage in these two distinct groups.…”
Section: Restricted Tcr Clonotypes Were Revealed In Pgd Compared With Ngd Patientsmentioning
confidence: 99%
“…As a consequence, AML patients—and especially patients with refractory disease or relapse after HSCT—display higher frequencies of exhausted T cells compared to healthy donors [ 12 – 19 ]. The malfunctioning T cell space in AML is also characterized by a general down-regulation of genes involved in T cell activation [ 20 ], as well as a skewed T cell repertoire with reduced diversity compared to healthy donors [ 19 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As we have previously discussed, thymus involution has been known to result in limited TCR diversity. Several groups have similarly reported restricted TCR repertoire diversity and skewed oligoclonal ab + and gd + T-cell pools in AML (74)(75)(76)(77). Notably, recent studies have shown restricted expression and oligoclonal expansion of certain Vb subfamily T cells, such as PD-1 + Vb T cells in patients with AML and CML (76,77).…”
Section: Thymus' Role In Clonotype Tcr Diversitymentioning
confidence: 98%